The Influence of Learning Methods and Cognitive Style on the Ability to Understand English Texts About Islam in Students - Dilo, Asna Usman (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This article aims to explore the impact of learning methods and cognitive styles on the ability to read Islamic texts in English. This study utilized an experimental method with a factorial design. The findings of this study can be summarized as follows: (1) The group of students who received learning with inquiry method showed a higher ability to read Islamic text in English compared to students who received the expository method; (2) The ability to read Islamic text in English was higher in the group of students with field-dependent cognitive style compared to students who had field-dependent cognitive style; (3) There was an interaction between learning method and cognitive style that affected the ability to read Islamic text in English; (4) The ability to read Islamic text in English taught with inquisitive method is higher than that taught with expository method in the group of students who have field-independent cognitive style; (5) Students with field-independent cognitive style show higher ability to read Islamic text in English compared to students who have field-dependent cognitive style, especially in the group of students who get learning with inquisitive method.